Touristic and Environmental Impacts of Historical Towns: The Reflections Of Spaces In Traditional Diyarbakir Architecture - Can Tuncay Akin; Mucahit Yildirim (European Regional Science Association (ERSA), 2006)
For the sustainability of historical towns and traditional buildings those are no longer feasible, an adaptive use must be given. This adaptive use must be convenient with socio-economic and cultural structure of the historical site. The most popular way for the maintenance of the historical site is the tourism activity. The case study held on for this reason is the historical town of Diyarbakýr. The town is surrounded by old city walls. The black basalt walls are perfect examples of the mediaeval architecture. Although some of the walls were from Roman, and even earlier times, the present walls date back to early Byzantine times. The main from civil architecture examples inside the walls are the traditional houses which are relevant with user requirements, desirability; habits of users are connected with socio-economic and socio-cultural values. Social experience, visions, believes, ethical principles are sourced from nature and living styles have affected the traditional Diyarbakýr housing architecture. The reflections of culture and civilization with integration of environment and material in physical space can be seen in traditional Diyarbakýr houses. Climatic conditions and social structure have played an important role in the shaping of the interior and exterior spaces of the traditional Diyarbakýr houses. There are few examples of restored houses in the old town. Some of them have become museum being due to the birth place of very popular writers and poets in them. The large houses which oriented for the patriarchal family style lost their function in the contemporary life style. Some of them can not be conserved as a house as before because of being too large for a small family. Some adaptive uses must be given for them concerning: gaining these 100-150 years buildings which lose partly their function world tourism and world cultural heritage, by giving new functions to them conservation of these buildings providing new usage, conservation of historical environment, by distinguishing different functional groups according to necessities considering location and size of the buildings in the historical town by means of building determination work economical evaluation The necessity of giving new function to buildings those do not meet the need due to changing social environment The reuse of the buildings by relevant techniques not only in building scale also in historical town scale. The other structures that have already lost their original uses and no longer feasible in the medieval town are the hamams, the inns and old bazaar where the hand crafts production are made must be protected. For example, by means of production of some touristic handcrafts and selling them inside, restaurants or hostels in those traditional houses in order to get the authentic atmosphere. The aim of the study is to preserve those structures for a sustainable conservation and the very convenient way to do it is using them for tourism. In order to give an adaptive use for these structures the analysis of the existing structures has to be made and the requirements of the tourism innovations have to be considered.
Keywords: 330